(untitled) (Singaporean Journal of Business Economics and Management, 2018)
Marketing research is a critical part of marketing decision making, it helps in improving management decision making by providing relevant, accurate, and timely information. Every decision poses unique needs for information, and relevant strategies can be developed based on information gathered through marketing research in action. Too often, marketing research is considered narrowly as the gathering and analyzing of data for someone else to use (Kotler & Kevin, 2012). However, firms can actually achieve and sustain a competitive advantage through the creative use of market information generated by marketing research. Hence, marketing research is defined as information input to decisions, not simply the evaluation of decisions that have been made. Market research alone, however, does not guarantee success; the intelligent use of market research is the key to business achievement. A competitive edge is more the result of how information is used rather than who does or does not have the information (Paurav, 2008). American Marketing Association (2005) opine that Marketing research is the function that links the consumer, customer and public to the marketer through information information used to identify and define marketing opportunities and problems; generate, refine, and evaluate marketing actions; monitor marketing performance; and improve understanding of marketing as a process. Marketing research specifies the information required to address these issues; designs the method for collecting information; manages and implements the data-collection process; analyzes the results; and communicates the findings and their implications.